2016
DOI: 10.1016/j.egypro.2016.11.110
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of CAES Systems Integrated into Gas-Steam Combined Plants

Abstract: In the present paper, an energy storage concept based on the integration of a Compressed Air Energy Storage system into a Gas Steam Combined Cycle plants is investigated. The integration of CAES results in a noticeable power augmentation in respect to normal GSCC plant operations. Being such a power increase obtained without using additional fuel, the storage system can be compared to PHS, BES and A-CAES. Two CAES integrated into medium size GSCC plants arranged with Aero Derivative and Heavy Duty Gas Turbines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In the previously cited author's paper [17], the integrated system storage efficiency was evaluated according to the following formula:…”
Section: Technical Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the previously cited author's paper [17], the integrated system storage efficiency was evaluated according to the following formula:…”
Section: Technical Considerationsmentioning
confidence: 99%
“…In order to explore the practical feasibility of the proposed system, a techno-economic analysis aimed at assessing plant performance and investment costs has been carried out [17]. Results have shown that, despite the relatively high investment costs and the storage efficiency being less than those featuring alternative storage approaches, the proposed system may be considered of interest due to the long life duration and to the proven technologies available for the key plant components.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations